﻿Description and phylogenetic analysis of two new Episinus (Araneae, Theridiidae) species from China - Fengjie Liu; Ingi Agnarsson; Jie Liu; Yang Zhu (ZooKeys, 2022)
The spider genus Episinus Walckenaer, 1809 currently contains 66 species worldwide, mostly in warm temperate to tropical areas. This paper describes two new Chinese Episinus species: E. ornithorrhynchus sp. nov. (♂♀) and E. papilionaceous sp. nov. (♀). We add these two new and one known Episinus species to the phylogenetic data matrix of Liu et al. 2016 and reanalyze the data. The new phylogeny recovers the monophyly of Episinus and supports its division into two groups, a finding also supported by morphology.